Redesain Visual Identity Azyanu Batik - Hidayatul Hasanah; Fauzan Aulia (Lembaga Pengembangan Kinerja Dosen, 2023)
Azyanu Batik is an MSME engaged in the field of batik art based on local Minangkabau culture with